Simulation versus real-world performance: a direct comparison of emergency medicine resident resuscitation entrustment scoring - Weersink, Kristen (Adv Simul (Lond), 2019)
BACKGROUND: Simulation is increasingly being used in postgraduate medical education as an opportunity for competency assessment. However, there is limited direct evidence that supports performance in the simulation lab as a surrogate of workplace-based clinical performance for non-procedural tasks such as resuscitation in the emergency department (ED). We sought to directly compare entrustment scoring of resident performance in the simulation environment to clinical performance in the ED. METHODS: The resuscitation assessment tool (RAT) was derived from the previously implemented and studied Queen’s simulation assessment tool (QSAT) via a modified expert review process. The RAT uses an anchored global assessment scale to generate an entrustment score and narrative comments. Emergency medicine (EM) residents were assessed using the RAT on cases in simulation-based examinations and in the ED during resuscitation cases from July 2016 to June 2017. Resident mean entrustment scores were compared using Pearson’s correlation coefficient to determine the relationship between entrustment in simulation cases and in the ED. Inductive thematic analysis of written commentary was conducted to compare workplace-based with simulation-based feedback. RESULTS: There was a moderate, positive correlation found between mean entrustment scores in the simulated and workplace-based settings, which was statistically significant (r = 0.630, n = 17, p < 0.01). Further, qualitative analysis demonstrated overall management and leadership themes were more common narratives in the workplace, while more specific task-based feedback predominated in the simulation-based assessment. Both workplace-based and simulation-based narratives frequently commented on communication skills. CONCLUSIONS: In this single-center study with a limited sample size, assessment of residents using entrustment scoring in simulation settings was demonstrated to have a moderate positive correlation with assessment of resuscitation competence in the workplace. This study suggests that resuscitation performance in simulation settings may be an indicator of competence in the clinical setting. However, multiple factors contribute to this complicated and imperfect relationship. It is imperative to consider narrative comments in supporting the rationale for numerical entrustment scores in both settings and to include both simulation and workplace-based assessment in high-stakes decisions of progression. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s41077-019-0099-4) contains supplementary material, which is available to authorized users.